Comparative Analysis of Sodium Hexa-titanate (Na2Ti6O13) & Sodium-Potassium Hexa-titanate (Na1.5K0.5Ti6O13). (March 2020) - Alam, N; Khatoon, T; Chandel, V S; Azam, A; Rashmi,
Abstract: The present paper discusses the synthesis and characterization of Sodium Hexatitanate (NHT) and Sodium-Potassium Hexa-titanate (NKHT) by solid state reaction method. The phase of the synthesized material was confirmed by XRD and the particle size has been calculated using Debye-Scherrer relation. Morphology of the surface and dimensions of the crystals have been analysed using FE-SEM analysis at different magnification. EDS analysis has also been done for elemental analysis of Sodium Hexa-titanate and Sodium Potassium Hexa-titanate. IR spectra has been recorded for getting various vibration modes of the samples.